Iron(II) catalyzed hydrophosphination of isocyanates - Sharpe, Helen R.; Geer, Ana M.; Lewis, William; Blake, Alexander J.; Kays, Deborah L. (Wiley-VCH Verlag, 2017)
The first transition metal catalyzed hydrophosphination of isocyanates is presented. The use of low-coordinate iron(II) precatalysts leads to an unprecedented catalytic double insertion of isocyanates into the P-H bond of diphenylphosphine to yield phosphinodicarboxamides [Ph2PC(=O)N(R)C(=O)N(H)R], a new family of derivatized organophosphorus compounds. This remarkable result can be attributed to the low-coordinate nature of the iron(II) centres whose inherent electron deficiency enables a Lewis-acid mechanism in which a combination of the steric pocket of the metal centre and substrate size determines the reaction products and regioselectivity.